Primary Malignant Melanoma of Vagina: The Options of Management. - Ng, BK; Lim, PS; Ng, YL; Kew, TY; Abdul Kadir AK,; Hatta M, (Department of Surgery, UKM Medical Centre, 2014)
Primary malignant melanoma of the vagina is rare but aggressive. Various treatment options include surgery and adjuvant therapy has been advocated but the outcome remained unpredictable. Standard treatment protocol is yet to be established. We report a case of 54-year-old, Para 4+1, with malignant melanoma of the vagina. She underwent wide local excision but the surgical margin was not clear of malignant cells, hence adjuvant radiotherapy was given. Combination chemotherapy was initiated subsequently as her disease disseminated. She succumbed later due to septicaemic shock. The treatment options for vaginal melanoma were reviewed.